Հակամարտությունների մեջ ներքաշված փոքր պետությունների դիվանագիտությունը ԵԱՀԿ Աստանայի 2010 թ. գագաթնաժողովում - Գրիգորյան, Արամայիս (YSU Journal of International Affairs, 2017)
In 1999 after the Istanbul summit, noOSCE summit was held for about 11 years. During its chairmanship, Kazakhstan initiated holding a new OSCE summit. Throughout the summit, both meetings of experts and the adoption of the final declaration were maintained up to the tense atmosphere. The most sensitive issues were related to the unresolved conflicts. The summit, which works based on consensus system, faced with the problem of failure because of a small number of states had sought to introduce preferential conditions for the final declaration. Finally, member states were able to accept a compromise to adopt the final declaration.
Keywords: OSCE summit in Astana, Astana 2010, small states, the Final Declaration of the OSCE Summit, the unresolved conflicts, Nagorno Karabakh, Transnistria, Abkhazia, South Ossetia